Do Nonexecutive Employees Have Valuable Information? Evidence from Employee Stock Purchase Plans - Babenko, Ilona; Sen, Rik (Management Science, 2016)
Using novel data on employee stock purchase plans (ESPPs), we show that aggregate purchases of company stock by lower-level employees predict future stock returns. Firms in the top quartile of ESPP purchases outperform those in the bottom quartile by 10% in the year after purchase. The relation between ESPP purchases and future stock returns is stronger for firms with high information asymmetry. Furthermore, we find that high ESPP purchases are associated with a lower likelihood of breaks in strings of consecutive earnings increases, as well as higher future sales growth and more innovation. These findings support the hypothesis that lower-level employees have information about future firm performance. We examine and reject a number of alternative explanations. Our results have implications for firms using employees as a source of capital, accounting issues related to expensing of equity-based compensation, and disclosure policy. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2015.2226 . This paper was accepted by Wei Jiang, finance.